Предмет: Алгебра,
автор: LYLYKO
Прошу помочь~
Нужно решить уравнение:
Приложения:
Ответы
Автор ответа:
0
замена переменной: х^2+х+1=t
тогда х^2+х+2=(х^2+х+1)+1
Получим уравнение с переменной t:
t*(t+1)=12
t^2+t-12=0
t1=-4, t2=3
Обратная замена:
t1=-4, x^2+x+1=-4, x^2+x+5=0
D<0, корней нет
t2=3, x^2+x+1=3, x^2+x-2=0
x1=-2, x2=1
Ответ: х1=-2, х2=1
Автор ответа:
0
Решение на прикрепленном фото
Приложения:
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: tetanatiholaz923
Предмет: Литература,
автор: Gjfidki4
Предмет: Математика,
автор: tatiana1910